Scrutinizing the double superconducting gaps and strong coupling pairing in (Li1−xFex)OHFeSe - Zengyi Du (Nature Communications, 2016)
Whilst superconductivity is understood to emerge when electronic pairing allows for conduction without resistance, the mechanism at work in Fe-based superconductors is unclear. Here, the authors address the details of Fermi surfaces and associated gaps as well as the pairing mechanism of (Li1−xFex)OHFeSe via scanning tunnelling methods.